2020
DOI: 10.1039/d0ta07706b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing surface oxygen retention through theory-guided doping selection in Li1−xNiO2 for next-generation lithium-ion batteries

Abstract: Using a collaborated in silico and experimental approach, we designed Sb-doped LiNiO2 with improved surface oxygen retention and electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 74 publications
(79 reference statements)
2
59
0
Order By: Relevance
“…[4][5][6][7][8] Particularly, with the discovery of effective dopants that can inhibit oxygen loss in deep charged states, doped lithium nickelate (LiNiO 2 ; LNO) has recently become one of the most promising high-energy cathode materials for LIBs because of their high specific energy, long cycle life, and reduced cobalt content. [9][10][11][12] Despite extensive electrochemical studies on this system in the 1990s [13][14][15] and recent renewed interest, 7,[16][17][18] the intrinsic cycling instability which involves complex degradation behaviors of this material has plagued its commercialization. For example, the extraction of Li from LNO causes a detrimental phase transformation that involves considerable volume shrinkage and thereby deteriorated capacity retention and structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Particularly, with the discovery of effective dopants that can inhibit oxygen loss in deep charged states, doped lithium nickelate (LiNiO 2 ; LNO) has recently become one of the most promising high-energy cathode materials for LIBs because of their high specific energy, long cycle life, and reduced cobalt content. [9][10][11][12] Despite extensive electrochemical studies on this system in the 1990s [13][14][15] and recent renewed interest, 7,[16][17][18] the intrinsic cycling instability which involves complex degradation behaviors of this material has plagued its commercialization. For example, the extraction of Li from LNO causes a detrimental phase transformation that involves considerable volume shrinkage and thereby deteriorated capacity retention and structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, a substantial contract of the c-lattice near the end of charge (SOC > ~75 %), i. e., due to H2-H3 phase transition, [28][29][30][31] is universally demonstrated to be the leading cause to the structural degradation of LNO. What is worse is the oxygen evolution, despite under active debate over its underlying mechanisms and reversibility, [24,30,32,33] accompanying the severe lattice distortion. While most studies [28][29][30][34][35][36] employ in situ/operando X-ray diffraction to monitor the structural evolution of LNO (or Nirich cathodes), little attention is paid to the discussion of local Li/Ni environments, for example, Li/NiÀ O bond lengths, as a function of Li content.…”
Section: Introductionmentioning
confidence: 99%
“…can stabilize the lattice oxygen owing to the strong electron hybridization effect with the oxygen in the layered oxide system. 74,75 In addition, experimental studies have shown that these dopants enhanced the Ni-rich layered cathode cyclability by alleviating the lattice contraction, crack propagation, oxygen evolution, and surface reconstruction. [2][3][4][5] In particular, the stabilization of lattice oxygen by Ti doping has been previously evidenced by mRIXS and DFT calculation, with similar results as those for Zr doping.…”
Section: Journal Name Articlementioning
confidence: 99%